SHPS-1 regulates integrin-mediated cytoskeletal reorganization and cell motility - Inagaki, Kenjiro (Oxford University Press, 2000)
The transmembrane glycoprotein SHPS-1 binds the protein tyrosine phosphatase SHP-2 and serves as its substrate. Although SHPS-1 has been implicated in growth factor- and cell adhesion-induced signaling, its biological role has remained unknown. Fibroblasts homozygous for expression of an SHPS-1 mutant lacking most of the cytoplasmic region of this protein exhibited increased formation of actin stress fibers and focal adhesions. They spread more quickly on fibronectin than did wild-type cells, but they were defective in subsequent polarized extension and migration. The extent of adhesion-induced activation of Rho, but not that of Rac, was also markedly reduced in the mutant cells. Activation of the Ras–extracellular signal-regulated kinase signaling pathway and of c-Jun N-terminal kinases by growth factors was either unaffected or enhanced in the mutant fibroblasts. These results demonstrate that SHPS-1 plays crucial roles in integrin-mediated cytoskeletal reorganization, cell motility and the regulation of Rho, and that it also negatively modulates growth factor-induced activation of mitogen-activated protein kinases.